Active site synergy of the mixed-phase cobalt diselenides with slight lattice distortion for highly reversible and stable lithium oxygen batteries. (30th November 2021) - Li, Minglu; Shu, Chaozhu; Hu, Anjun; Yan, Yu; He, Miao; Long, Jianping
Highlights: The heterogeneous interface inside c-CoSe2 /o-CoSe2 strengthened the covalent bond between co and se ions, thus improving the lattice strength and enhancing the stability of the catalyst. The modulated interface electron transfer and the optimized adsorption capabilities of the c-CoSe2 /o-CoSe2 for reactants and intermediates lead to the remarkable improvement of reversibility of the LOBs. The DFT calculation results show that the reversibility of LOBs is significantly improved by adjusting the interface electron transfer of the reactants and optimizing the adsorption capacity of the intermediates. The discharge specific capacity of the battery is as high as 23, 878 mA h g − 1 and it can cycle steadily for about 1410 h. Abstract: Many non-precious metal-based catalysts with high intrinsic activity for catalytic reactions are prone to structural degradation in practical application, which leads to poor stability. In this work, we propose c-CoSe2 /o-CoSe2 as the oxygen electrode of lithium-oxygen batteries (LOBs) to improve its cycle stability. The heterogeneous interface inside c-CoSe2 /o-CoSe2 leads to an increase in the covalence bonds between Co and Se ions, which greatly enhances the robustness of the crystal lattice, thereby improving the stability of the catalyst. In addition, the strong interaction between the mixed phases is favorable for adjusting the electron density around the active sites and boosting oxygen electrode kinetics. Moreover, the epitaxial growth of o-CoSe2 on c-CoSe2 will cause abundant heterogeneous interfaces and slight lattice distortion along the interfaces, thereby providing sufficient catalytic reaction sites. The DFT calculation results show that the optimized adsorption of intermediates at the heterogeneous interface plays an important role in boosting oxygen electrode reactions and improving the electrochemical performance of LOBs. The experimental results show that LOBs with the c-CoSe2 /o-CoSe2 electrodes exhibit outstanding performance, including large specific capacity of about 23, 878 mA h g − 1, high coulombic efficiency of up to 93.66%, and excellent stability of over 176 cycles (1410 h). Graphical abstract: Image, graphical abstract